2012
DOI: 10.1016/j.abb.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutants induce transcription of NF-κB2 in H1299 cells through CBP and STAT binding on the NF-κB2 promoter and gain of function activity

Abstract: Cancer cells with p53 mutations, in general, grow more aggressively than those with wild-type p53 and show “gain of function”(GOF) phenotypes such as increased growth rate, enhanced resistance to chemotherapeutic drugs, increased cell motility and tumorigenicity; although the mechanism for this function remains unknown. In this communication we report that p53-mediated NF-κB2 up-regulation significantly contributes to the aggressive oncogenic behavior of cancer cells. Lowering the level of mutant p53 in a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 47 publications
2
54
0
Order By: Relevance
“…Several laboratories have demonstrated that GOF p53 accelerates cell proliferation and tumor growth in comparison with p53-null or GOF p53-knockdown cells (12,15,16). Since the data presented above indicate that GOF p53 requires its TADs to increase origin firing and to prevent replication fork col- mental Figure 6).…”
Section: 4mentioning
confidence: 98%
See 3 more Smart Citations
“…Several laboratories have demonstrated that GOF p53 accelerates cell proliferation and tumor growth in comparison with p53-null or GOF p53-knockdown cells (12,15,16). Since the data presented above indicate that GOF p53 requires its TADs to increase origin firing and to prevent replication fork col- mental Figure 6).…”
Section: 4mentioning
confidence: 98%
“…Cells were partially synchronized by density arrest and replating and sequentially labeled with IdU and chlorodeoxyuridine (CldU) at early S phase. Cellular genomic DNA was then spread on slides, and replicating DNA fibers were detected by immunostaining of incorporated IdU and CldU using with p53-null or -knockdown cells (15,16) and upregulates expression of cell-proliferating genes (27). Therefore, experiments were carried out to determine whether GOF p53 hastens the time of S phase entry compared with p53-null cells.…”
Section: Gof P53 Mutation and Loss Of Wt P53 Hasten Time Of S Phase Ementioning
confidence: 99%
See 2 more Smart Citations
“…Both transfection and luciferase assays were as described previously in triplicate. 57 Chromatin immunoprecipitation. ChIP was performed as described.…”
Section: 55mentioning
confidence: 99%